From the Bench to the Field in Low‐Cost Diagnostics: Two Case Studies. Issue 20 (27th April 2015) - Kumar, Ashok A.; Hennek, Jonathan W.; Smith, Barbara S.; Kumar, Shailendra; Beattie, Patrick; Jain, Sidhartha; Rolland, Jason P.; Stossel, Thomas P.; Chunda‐Liyoka, Catherine; Whitesides, George M.
Abstract Despite the growth of research in universities on point‐of‐care (POC) diagnostics for global health, most devices never leave the laboratory. The processes that move diagnostic technology from the laboratory to the field—the processes intended to evaluate operation and performance under realistic conditions—are more complicated than they might seem. Two case studies illustrate this process: the development of a paper‐based device to measure liver function, and the development of a device to identify sickle cell disease based on aqueous multiphase systems (AMPS) and differences in the densities of normal and sickled cells. Details of developing these devices provide strategies for forming partnerships, prototyping devices, designing studies, and evaluating POC diagnostics. Technical and procedural lessons drawn from these experiences may be useful to those designing diagnostic tests for developing countries, and more generally, technologies for use in resource‐limited environments.